Synthesis and characterization of novel polymer-hybrid silver nanoparticles and its biomedical study - Verma, Suresh Kumar; Jha, Ealisha; Kiran, K. J.; Bhat, Suresh; Suar, Mrutyunjay; Mohanty, P. S. (Materials Today: Proceedings, 2016)
Hybrid polymer metal nanoparticles have advantages over conventional metal nanoparticles with respect to their stability, chemical resistance, antibacterial activity and drug delivery properties. In the current work, we have synthesized novel stimuli-responsive polymer hybrid silver nanoparticles using green synthesis method, where the plant extract is used as a reducing agent in the synthesis. Encapsulating metal nanoparticles with stimuli-responsive soft-polymeric system is novel and provides additional versatility whose functions and properties can be tailored by controlling any of the stimuli such as pH, temperature, ionic strength with respect to their antibacterial activity and physiological condition. Moreover, green synthesis methods have advantages over conventional methods involving chemical reducing agents that are often associated with environmental toxicity because of their enhanced antibacterial and other biological effects. The synthesized hybrid particles were characterized using Dynamic light scattering, UV-Visible spectroscopy and Small angle x-ray scattering. Further, we have investigated the antibacterial and cytotoxicity effect of these hybrid particles against different bacterial cells ( Salmonella) and mammalian cell lines (HCT116) respectively. These results are discussed in the light of previous studied work and these results suggest that our synthesized polymer hybrid nanoparticles are more antibacterial and less cytotoxic than the usual silver nanoparticles. (C) 2015Elsevier Ltd.All rights reserved.
Keywords: Antibacterial effect; Cytotoxicity; Polymeric hybrid particless; silver nanoparticles

Self-supported super-hydrophilic interconnected nanospikes and particles of MoS2-Ni3S2/NF with optimum d-band center for anion exchange membrane water electrolyzer - Kumar, Yogesh; Barik, Sidharth; Samudre, Nikhil S.; Kharabe, Geeta Pandurang; Chauhan, Inderjeet; Manna, Narugopal; Bhat, Suresh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
There is an imperative need for highly efficient electrocatalysts for cost-effective hydrogen production. Herein, a self-supported, hybrid composite as a bifunctional electrocatalyst is introduced. This is achieved by in situ growth of MoS2-Ni3S2 on nickel foam (NF), designated as MoS2-Ni3S2/NF, synthesized by a facile one-step hydrothermal synthesis method. MoS2-Ni3S2/NF exhibits low overpotentials of only 187 and 146 mV for OER and HER, respectively, to achieve a current density of 10 mA cm-2 in 1 M KOH. The practical application of the designed bifunctional electrocatalyst is verified by constructing the MoS2-Ni3S2/NF || MoS2-Ni3S2/NF symmetrical membrane electrode assembly (MEA) of 4 cm2 working area for the anion exchange membrane water electrolyzer. The system shows continuous electrolysis for the monitored 48 h duration. For OER, an optimum d-band center of -1.66 eV for the heterostructure is calculated from the Density Functional Theory (DFT) studies. The factors like the unique structure of the electrocatalyst, enhanced hydrophilicity, improved electrochemically accessible number of sites (ECASs), and optimum d-band center, are expected to be the primary contributors to the system's improved performance. Thus, the present finding unveils a straightforward synthesis approach for creating a stable electrocatalyst for advancing commercial water electrolysis in the realm of renewable electrochemical energy conversion.
Keywords: AEM; d-band center; electrolyzer; HER; OER

Self-healing hydrogel electrolyte enabled by dynamic polar covalent and noncovalent interactions for high-performance rechargeable zinc-metal batteries: a leap toward sustainable energy storage - Puthiyaveetil, Priyanka Pandinhare; Kurian, Rachna Maria; Samudre, Nikhil S.; Balasubramanian, Rajalakshmi; Torris, Arun; Pockil, Fayis Kanheeram; Bhat, Suresh; Ajithkumar, T. G.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Advanced Energy Materials, 2026)
Hydrogel polymer electrolytes with superior multifunctional properties are promising alternatives to aqueous electrolytes for resolving interfacial issues in rechargeable zinc-metal batteries. In this study, an intrinsic self-healing hydrogel polymer electrolyte (PHBC-4) is synthesized, engineered through an integrated approach involving the polar covalent (B & horbar;O bond), hydrogen-bond (polyvinyl alcohol-hydroxypropyl methylcellulose interface), and coordination-type (Zn & horbar;O) interactions to enable self-healing functionality. The PHBC-4 has demonstrated high ionic conductivity (4.6 x 10-2 S cm-1), good oxidative stability (2.3 V vs Zn|Zn2+), a high cation transference number (0.89), superior tensile strength (0.32 MPa), and an impressive healing efficiency of 93% achieved just within 5 min, confirming its robust self-healing capability. In Zn||Zn symmetric cells, it effectively suppresses dendrite growth, ensuring stable cycling for over 1032 h with an areal capacity of 1.0 mAh cm-2 at a current density of 1.0 mA cm-2. When paired with a Zn-doped MnO cathode in the rechargeable homemade pouch cell, the system delivers a high specific capacity of 160 mAh g-1 at 0.10 A g-1 and cycling stability up to 493 charge-discharge cycles at 2.0 A g-1. The self-healing ability of PHBC-4 HGPE is confirmed in a homemade pouch cell via OCV and charge-discharge tests, demonstrating stable performance. The DFT studies confirm molecular-level interactions within the hydrogel heterostructure.
Keywords: dendrite inhibition; flexible rechargeable zinc metal battery; high cation transference number; self-healing hydrogel polymer electrolyte